Performance Management System In Improving Teacher Productivity In Senior High School - Eka Diana; Nudia Fariha; Moh Rofiki (Jurnal Ilmu Sosial Mamangan, 2024)
The performance of teachers has a significant impact on the overall performance of educational institutions. This research focuses on the implementation of the performance management system to improve teacher productivity at Nurul Jadid High School. A qualitative approach is the approach used in this research, while a case study is the type of research. In addition, this research was conducted at an educational institution within the boarding school environment, namely Nurul Jadid High School. Research data were collected through participant observation, in-depth interviews, and documentation studies. Informants of the principal, vice principal, and teachers were used as primary data, while secondary data were obtained through national and international journals. Data analysis was carried out in a series of sequential stages, starting with data reduction, data display, and conclusion drawing. The results of the research performance management system are implemented through several stages, starting with the planning system, implementation system, evaluation system, and reward system. In addition, the implementation increases teacher productivity in carrying out their duties and functions.